2020
DOI: 10.1002/cbdv.201900548
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐Embedded Molecular Dynamics Simulation Model for Exploring the Reverse Prostaglandin D2 Agonism of CT‐133 towards CRTH2 in the Treatment of Type‐2 Inflammation Dependent Diseases

Abstract: Chemoattractant receptor‐homologous molecule expressed on Th2 cells (CRTH2) has been involved in several inflammation dependent diseases by mediating the chemotaxis of pro‐inflammatory cells in response to allergy and other responses through PGD2 ligation. This CRTH2‐PGD2 signaling pathway has become a target for treating allergic and type 2 inflammation dependent diseases, with many inhibitors developed to target the PGD2 binding pocket. One of such inhibitors is the ramatroban analog, CT‐133, which exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…However, CRTH2 stands apart as it operates without conventional activation [41,61]. Molecular dynamics studies have revealed consistent transmembrane conformations among antagonists, agonists, and CRTH2 alone [41,58,62], except for the behavior of helix 8 [61,62]. This helix, upon binding of an agonist, will undergo compaction to inhibit arrestin recruitment.…”
Section: Evaluation Of Structural Inactivation Of Target Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, CRTH2 stands apart as it operates without conventional activation [41,61]. Molecular dynamics studies have revealed consistent transmembrane conformations among antagonists, agonists, and CRTH2 alone [41,58,62], except for the behavior of helix 8 [61,62]. This helix, upon binding of an agonist, will undergo compaction to inhibit arrestin recruitment.…”
Section: Evaluation Of Structural Inactivation Of Target Receptorsmentioning
confidence: 99%
“…Intracellular: The only known structural change is that the agonist causes helix 8 to undergo compaction, inhibiting arrestin recruitment [61,62].…”
Section: Crth2mentioning
confidence: 99%
See 1 more Smart Citation
“…The binding affinity for GPR44, estimated through a MM/PBSA-based approach, showed total free energy values of -67.50 kcal/mol for CT-133 and -50.12 kcal/mol for PGD 2 . The lower binding energy has been attributed to the 7-azaindole group that causes CT-133 to bind more favorably to GPR44 than PGD 2 [ 89 ].…”
Section: Ramatroban-based Analogues For Potential Gpr44 Bindingmentioning
confidence: 99%